Enhanced Nonenzymatic Ligation of Homopurine Miniduplexes: Support for Greater Base Stacking in a Pre‐RNA World. Issue 1 (6th December 2012) - Kuruvilla, Elizabeth; Schuster, Gary B.; Hud, Nicholas V.
<x xml:space="preserve">Abstract</x> The ancestors of RNA? There is a long‐standing proposal that contemporary nucleic acids might have evolved from RNA‐like polymers that utilized only purine–purine base pairs. Here we demonstrate the great advantage that increased nucleobase stacking area provides for nonenzymatic ligation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>